"Phonetic Harmony in Algerian Folk Riddles" - guerfa, zina (El Omda in Linguistics and Discourse Analysis, 2018)
Resume The sound has an audio value, and the word consists of several voices. The study of the word requires studying its linguistic sounds and its relation to the meanings. The linguistic sounds are classified in the human vocal system on the basis of their exits. Each voice or letter has a general or special character, this latter is how the letter is generated and exits from its output, its purpose is to distinguish characters from each other, especially homogeneous letters. It is necessary to have a link between the word or the sound and what it means, the words are sounds that gain the significance of the bell of their voices; the phonetic significance is established, and we have tried in this article to apply the sound harmony on special popular text which are popular puzzles; So that this type of discourse has a great deal of study in order to highlight the beauty and professionalism and accuracy of its formulation.